Feasibility study of a non-destructive fruit maturity testing system on banana utilizing capacitive properties - Zulkifli, Husin; Abdul Hallis, Abdul Aziz; R. Badlishah, Ahmad (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org